Cavity-Suppressing Electrode Integrated with Multi-Quantum Well Emitter: A Universal Approach Toward High-Performance Blue TADF Top Emission OLED - Jang, Il Gyu; Murugadoss, Vignesh; Park, Tae Hoon; Son, Kyung Rock; Lee, Ho Jin; Ren, WanQi; Yu, Min Ji; Kim, Tae Geun (Nano-Micro Letters, 2022)
A novel device structure for thermally activated delayed fluorescence (TADF) top emission organic light-emitting diodes (TEOLEDs) that improves the viewing angle characteristics and reduces the efficiency roll-off is presented. Furthermore, we describe the design and fabrication of a cavity-suppressing electrode (CSE), Ag (12 nm)/WO3 (65 nm)/Ag (12 nm) that can be used as a transparent cathode. While the TADF-TEOLED fabricated using the CSE exhibits higher external quantum efficiency (EQE) and improved angular dependency than the device fabricated using the microcavity-based Ag electrode, it suffers from low color purity and severe efficiency roll-off. These drawbacks can be reduced by using an optimized multi-quantum well emissive layer (MQW EML). The CSE-based TADF-TEOLED with an MQW EML fabricated herein exhibits a high EQE (18.05%), high color purity (full width at half maximum ~ 59 nm), reduced efficiency roll-off (~ 46% at 1000 cd m−2), and low angular dependence. These improvements can be attributed to the synergistic effect of the CSE and MQW EML. An optimized transparent CSE improves charge injection and light outcoupling with low angular dependence, and the MQW EML effectively confines charges and excitons, thereby improving the color purity and EQE significantly. The proposed approach facilitates the optimization of multiple output characteristics of TEOLEDs for future display applications. Highlights: 1 A blue thermally activated delayed fluorescence top-emission organic light-emitting diode (TEOLED) structure that combines a cavity-suppressing transparent electrode and a multi-quantum-well emissive layer is proposed. 2 The TEOLED exhibits high external quantum efficiency (18.05%), high color purity (full width at half maximum ~ 59 nm), reduced efficiency roll-off (~ 46% at 1000 cd m−2), and low angular dependence